REBRANDING TERMINAL GROGOL: WAJAH BARU TERMINAL GROGOL - Regan Vicgor Wijaya; Nafiah Solikhah (Jurusan Arsitektur dan Perencanaan, 2023)
The terminal is well known to all Jakartans as a public facility for finding public transportation modes according to their destination. Public transportation such as city buses and angkots use the terminal as a starting point and take passengers to other terminals and stopping points. Judging from the current conditions, public transportation modes at the terminal are less in demand as a result of technological developments in the transportation sector which make it easier for them to use other modes of transportation, for example, online taxis. This causes functional degradation at the terminal which can slowly disappear. The degradation that occurs in the terminal then has an impact on the environment which also becomes quieter and